Heterogeneity of neuroendocrine transcriptional states in metastatic small cell lung cancers and patient-derived models - Lissa, Delphine; Takahashi, Nobuyuki; Desai, Parth; Manukyan, Irena; Schultz, Christopher W.; Rajapakse, Vinodh; Velez, Moises J.; Mulford, Deborah; Roper, Nitin; Nichols, Samantha; Vilimas, Rasa; Sciuto, Linda; et al. (Nature communications, 2022)
Molecular subtypes of small cell lung cancer (SCLC) defined by the expression of key transcription regulators have recently been proposed in cell lines and limited number of primary tumors. The clinical and biological implications of neuroendocrine (NE) subtypes in metastatic SCLC, and the extent to which they vary within and between patient tumors and in patient-derived models is not known. We integrate histology, transcriptome, exome, and treatment outcomes of SCLC from a range of metastatic sites, revealing complex intra- and intertumoral heterogeneity of NE differentiation. Transcriptomic analysis confirms previously described subtypes based on ASCL1 , NEUROD1 , POU2F3 , YAP1 , and ATOH1 expression, and reveal a clinical subtype with hybrid NE and non-NE phenotypes, marked by chemotherapy-resistance and exceedingly poor outcomes. NE tumors are more likely to have RB1 , NOTCH , and chromatin modifier gene mutations, upregulation of DNA damage response genes, and are more likely to respond to replication stress targeted therapies. In contrast, patients preferentially benefited from immunotherapy if their tumors were non-NE. Transcriptional phenotypes strongly skew towards the NE state in patient-derived model systems, an observation that was confirmed in paired patient-matched tumors and xenografts. We provide a framework that unifies transcriptomic and genomic dimensions of metastatic SCLC. The marked differences in transcriptional diversity between patient tumors and model systems are likely to have implications in development of novel therapeutic agents. Molecular subtypes of small cell lung cancer characterized by neuroendocrine differentiation have been described in cell lines and primary tumors. The clinical implications of neuroendocrine subtypes in metastatic and relapsed tumors, and the extent to which the subtype distribution is recapitulated in patient-derived models remains unclear. Here, the authors integrated genomics and transcriptomics on 100 small cell cancers from a range of metastatic sites finding complex intra- and intertumoral heterogeneity, notably not recapitulated in patient-derived model systems, and distinct therapeutic vulnerabilities associated with neuroendocrine subtypes.